2017
DOI: 10.1016/j.jpha.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of penicillamine using Cu-modified graphene quantum dots synthesized from uric acid as single precursor

Abstract: A simple methodology was developed to quantify penicillamine (PA) in pharmaceutical samples, using the selective interaction of the drug with Cu-modified graphene quantum dots (Cu-GQDs). The proposed strategy combines the advantages of carbon dots (over other nanoparticles) with the high affinity of PA for the proposed Cu-GQDs, resulting in a significant and selective quenching effect. Under the optimum conditions for the interaction, a linear response (in the 0.10–7.50 µmol/L PA concentration range) was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…Figure S3C illustrates the differences in the GQD fluorescence according to the pH value, showing the maximum fluorescence at pH 7.5. GQD absorption (blue line), excitation (green line), and emission (orange line) spectra show characteristic profiles consistent with previous studies [26], as can be observed in Fig. S4.…”
Section: Characterization Of Gqdssupporting
confidence: 90%
See 2 more Smart Citations
“…Figure S3C illustrates the differences in the GQD fluorescence according to the pH value, showing the maximum fluorescence at pH 7.5. GQD absorption (blue line), excitation (green line), and emission (orange line) spectra show characteristic profiles consistent with previous studies [26], as can be observed in Fig. S4.…”
Section: Characterization Of Gqdssupporting
confidence: 90%
“…The relative quantum yield (QY) was calculated by measuring the fluorescence of GQDs prepared at 200°C as previously reported [26]. It was used quinine sulfate as the fluorophore of known QY [27] under the same experimental conditions since it is comparable with the ensuing GQDs.…”
Section: Measurement Of Quantum Yield Of Graphene Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…N-GQDs were synthesized from uric acid, by heating the precursor in concentrated sulfuric acid at 200 °C for 1 h [ 58 ], or d-glucose in the presence of 1-hexadecylamine at a temperature of only 60 °C, where single crystalline dots were detected [ 59 ]. N-GQDs have been isolated by hydrothermal treatment at 150 °C for 4 h with a glucose aqueous solution mixed with ammonia and H 2 O 2 [ 60 ].…”
Section: Graphene Quantum Dots Synthetic Strategiesmentioning
confidence: 99%
“…Very recently, a suitability of Cu-doped and Cu-decorated GSs as powerful adsorbents has been demonstrated for a series of organic molecules employing QTAIM analysis [20,22]. From the synthetic point of view, several experimental attempts to prepare graphene materials decorated with copper atoms [23][24][25], or covered with Cu 2+ cations [26] have been reported. Still, it has to be mentioned that the synthesis of Cu-GS units with well define dimension depends strongly on the reaction time, concentration, voltage, electric current and other conditions [23][24][25]27].…”
Section: Introductionmentioning
confidence: 99%